ANÁLISE CITOGENÉTICA E MOLECULAR EM PHLAEOTHIPIDEOS (THYSANOPTERA: PHLAEOTHIPIDAE) - Brito, Ricardo Oliveira (2011)
The order Thysanoptera comprises small insects known as thrips, which present different life histories and habits; they reproduce by haplodiploidy, and reached the status of prague by their feeding damage to plants. Their systematics, taxonomy and phylogenetic relationships are complicated, due to the small morphological variation among the taxa. Thus, this study aimed to analyze three species of the family Phlaeothripidae: Gynaikothrips uzeli, Liothrips sp. and Pseudophilothrips gandolfoi through conventional and molecular cytogenetics giving emphasis to the evolutionary processes that have occurred during the differentiation karyotype in the group, reinforcing the importance of cytogenetic studies as a tool for taxonomy of order, in addition to estimate genetic population parameters of G. uzeli. To that end, we analyzed the diploid number, the chromosome morphology, the distribution pattern of the heterochromatic regions, the chromosomes bearing Ag-NORs and performed mapping physical for cístrons of rDNA 18S. In addition, it was estimated the genetic variability and population structure of G. uzeli through the RAPD marker. The results obtained with the probe of 18S rDNA revealed a pair chromosomal bearer of RON in the three species, however, in G. uzeli only one of the elements of chromosomal 13 pair was marked. In addition, the results of cytogenetic analysis indicate that the genera Pseudophilothrips and Liothrips display strong similarities in their chromosomal complements. The low genetic variability, observed with the RAPD marker for G. uzeli, and result of the system of sexual determination haplodiploidy and ecological features. The cytogenetic analysis revealed differences that are difficult to observe the morphological level, demonstrating the importance of this methodology for systematic and taxonomy and clarification of complex evolutionary patterns presented in the order.